To subtract the given expressions, we must apply the distributive property and combine like terms.
First, let's simplify each part of the expression:
3b - 2c = 3b - 2c (no change)
6c + 2b = 2b + 6c (rearranged terms)
b + c = b + c (no change)
Now, let's subtract each of these simplified expressions:
(3b - 2c) - (6c + 2b) - (b + c)
= 3b - 2c - 6c - 2b - b - c
= (3b - 2b - b) - (2c + 6c + c)
= (3 - 2 - 1)b - (2 + 6 + 1)c
= 0b - 9c
= -9c
Therefore, the simplified expression is -9c.
Subtract: (3b−2c)−(6c+2b)−(b+c) pls explain
1 answer